Discourses of Women's Movements and Struggles in Muslim Women's Mass Media in 1912-1942 - Afghani, RP. M. Himam Awan; Saepudin, Didin; Rahman, Syaifur; Muarofah, Ulfiatul (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2025)
PurposeThis research aimed to reveal various discourses and narratives of womanhood that were popularly discussed in the era before Indonesian independence. In addition, it also tried to reveal the movement of women against oppression using writings published in various Muslim mass media. MethodIn this case, this research used a sociological approach and uses qualitative content analysis theory. The study made various mass media of Muslim women in 1912-1942 as the primary data sources. They were original archives that had been converted into microfilm. The data were analyzed using a sociological approach and critical discourse analysis. Findings/ResultThis research reveals that the oppression experienced by Muslim women both in the public and domestic spheres is the most frequently raised topic. This is because the limited access to education for women, the deep-rooted patriarchal culture, and the limited role of women in the public sphere were still closely attached to Indonesian society. ConclusionThe Muslim mass media becomes an effective tool in voicing women's voices, ranging from the polemic of polygamy practices, the importance of education for women, the position of women, to the narrative of women's involvement in combat.